Peran perpustakaan di sekolah dalam meningkatkan mutu pembelajaran - Kholisah, Umi Nurul Nurul (Maliki Interdisciplinary Journal, 2024)
The school library is an interesting means to help the teaching and learning process, as seen from the availability of various references or books, especially reading materials at school. then, the library plays a role in further information development with the aim that the library can be seen as something important in the world of education in schools. The type of research used is descriptive qualitative, namely research that describes the data obtained by the author from informants to obtain a clear and detailed picture of the role of libraries in schools in improving the quality of learning. The data collection technique used in this research is by reading literacy from journals, articles, and books. The purpose of doing this research is to find out the role of libraries in schools in improving the quality of learning.